APPLICATION OF THE K-MEANS CLUSTERING METHOD FOR PERFORMANCE ASSESSMENT BASED ON THE COMPETENCY OF EDUCATORS - Nababan, Marlince; Sinaga, Cristian Vieri; Napitupulu, Indra Wirayudha; Rahman, Adzisyah; -, Steven (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2023)
The ability of lecturers to teach for 1 (one) semester needs to be evaluated. Evaluation is a student assessment through a student academic information system. Review using the system is separate because many students need to care about the filled things. There the author tries to analyze the values ​​from the questionnaire results distributed to students using the Principal Component Analysis (PCA) technique and the K-Means method, where PCA reduces data. At the same time, K-Means assumed the values ​​closest to the study's results and concluded that of the 3 (three) clusters, the maximum distance was 0.5475 in cluster 1 and cluster 3.